1801 Tenn. Acts 260-261, ch. 22, § 6 - (:unkn) unknown (General Publisher, 1801)
Prohibited any person to ride or go armed to the terror of the people, or privately carry any dirk, large knife, pistol, or any other dangerous weapon. If the violator did not post a surety, the violation would be punished as. "breach of the peace or riot at common law."
--
Keywords: SURETY